Aqueous based synthesis of antimicrobial-decorated graphene - Wahid, M.; Stroeher, U.; Eroglu, Ela; Chen, X.; Vimalanathan, K.; Raston, C.; Boulos, R. (2015)
© 2014 Elsevier Inc. Ramizol® (1,3,5-tris[(1E)-2'-(4'-benzoic acid)vinyl]benzene) is a potent amphiphilic anti-microbial agent. It is essentially a planar molecule and can interact with the surface of graphene via extended p-p interactions. Herein we demonstrate the utility of Ramizol® in potentially acting as a molecular 'wedge' to exfoliate graphene and stabilise it in water. The non-covalent attachment of Ramizol® on the graphene surface enables release of Ramizol® by altering the pH of the solution. Furthermore, the stabilised composite material demonstrates antibacterial activity against Staphylococcus aureus which leads to potential in biomedical applications with graphene acting as a drug carrier as well as enhancing the structural strength of the composite material.